The political economy of international oil and the underdeveloped countries - Tanzer, Michael (Boston : Beacon Press, 1969)
The main focal point of this book, however, is the less obvious impact of oil on the vast majority of underdeveloped countries which are presently dependent upon imported oil.
Includes index
Bibliographical references included in "Notes" (p. 377-426)
occ 16/01/2019
Loans
Keywords: Petroleum industry and trade; Underdeveloped Countries